Causal association between gut microbiomes and different types of aneurysms: a Mendelian randomization study - Qiu, Youjia; Hou, Yucheng; Wei, Xingzhou; Wang, Menghan; Yin, Ziqian; Xie, Minjia; Duan, Aojie; Ma, Chao; Si, Ke; Wang, Zhong (Frontiers in Microbiology, 2024)
Background: Previous studies suggests that gut microbiomes are associated with the formation and progression of aneurysms. However, the causal association between them remains unclear.Methods: A two-sample Mendelian randomization was conducted to investigate whether gut microbiomes have a causal effect on the risk of intracerebral aneurysm (IA), thoracic aortic aneurysm (TAA) and abdominal aortic aneurysm (AAA), and aortic aneurysm (AA). Single nucleotide polymorphisms (SNPs) smaller than the locus-wide significance level (1 × 10 -5 ) were selected as instrumental variables. We used inverse-variance weighted (IVW) test as the primary method for the evaluation of causal association. MR-Egger, weighted median, weighted mode, and MR Pleiotropy Residual Sum and Outlier (MR-PRESSO) methods were conducted for sensitive analysis. The pvalue was adjusted by the false discovery rate (FDR) which adjust the results of multiple comparisons, a p < 0.05 and q < 0.1 was considered a significant causal association. Additionally, a p < 0.05 and q > 0.1 was considered a suggestive causal effect. Additionally, reverse MR was also performed to exclude the possibility of reverse causality. Results: The phylum Firmicutes (OR = 0.62; 95% CI, 0.48-0.81), class Lentisphaeria (OR = 0.75; 95% CI, 0.62-0.89), and order Victivallales (OR = 0.75; 95% CI, 0.62-0.89) have a causal protective effect on the risk of AAA. Additionally, class Verrucomicrobia, class Deltaproteobacteria, order Verrucomicrobiale, family Verrucomicrobiacea, genus Eubacterium rectale group, genus Akkermansia, and genus Clostridium innocuum group were negatively associated with the risk of different types of aneurysms, whereas class Negativicutes, order Selenomonadales, and genus Roseburia had positive causal association with different types of aneurysms (p < 0.05; q > 0.1). Further sensitivity analysis validated the robustness of our MR results, and no reverse causality was found with these gut microbiomes (p > 0.05).Our MR analysis confirmed the causal association of specific gut microbiomes with AAA, and these microbiomes were considered as protective factors. Our result may provide novel insights and theoretical basis for the prevention of aneurysms through regulation of gut microbiomes.